PERAN CUSTOMER FAMILIARITY PADA PRODUCT QUALITY, RETAIL SERVICES QUALITY DAN PRECIVED VALUE DALAM REPURCHASE INTENTION - M Trihudiyatmanto; Ndan Riono (Journal of Social Sustainability Management, 2021)
One of the theories about repurchase itention is customer behavior where customers respond positively to the quality of service of a company and intend to re-visit or consume the company's products again (Cronin, et al. 1992). This study examines antecedents of repurchase itention by using product quality, retail service quality and precived value as antecedents with the role of customer familiarity as an intervening variable. Questionnaires were distributed to 100 Ananda Store consumers who were sampled in Garung District, Wonosobo Regency. Regression analysis is used to test the relationship between variables. The results showed that all independent variables tested in this study had a significant effect on repurchase itention. And the customer familiarity variable is a variable that mediates all product quality, retail service quality and precived value variables to repurchase intention. Teori tentang repurchase itention salah satunya adalah perilaku pelanggan dimana pelanggan merespons positif terhadap kulitas pelayanan suatu perusahaan dan berniat melakukan kunjungan kembali atau mengkonsumsi kembali produk perusahaan tersebut (Cronin, dkk. 1992). Penelitian ini menguji anteseden repurchase itention dengan menggunakan product quality, retail services quality dan precived value sebagai anteseden dengan peran customer familiarity sebagai variabel intervening. Kuesioner dibagikan kepada 100 konsemuen Ananda Store yang menjadi sampel di Kecamatan Garung, Kabupaten Wonosobo. Analisis regresi digunakan untuk menguji hubungan antar variabel. Hasil menunjukkan bahwa semua variabel bebas yang diujikan dalam penelitian ini berpengaruh signifikan terhadap repurchase itention. Dan variabel customer familiarity merupakan variabel yang memediasi semua variabel product quality, retail services quality dan precived value terhadap repurchase intention.